The Determinants and Consequences of Tax Avoidance in Indonesia: The Effects of Top Management Characteristics and Capital Structure - Stevanus Pangestu; Irenius Dwinanto Bimo (Studi Akuntansi dan Keuangan Indonesia, 2018)
Tax avoidance is the lawful minimization of income tax by employing legal methods. This study aims to assess the effects of top management characteristics and capital structure on tax avoidance, measured with Effective Tax Rate (ETR). Our panel data comprise public manufacturing corporations, observed from 2010-2015 (n= 452). Based on our panel analysis using random effects model on EView, we find that tax avoidance: (i) is negatively influenced by independent directors (ii) is positively affected by foreign directors; (iii) is influenced by capital structure, measured with firm leverage, and (iv) positively affects current profitability, measured with Return on Equity. Meanwhile, the influence of female directors are found to be nonexistent. We also offer empirical evidence that board of directors’ characteristics influence tax avoidance through financing decisions. The findings of this study suggest that firm capital structure determination is motivated by the intention to avoid taxes. Keywords: board characteristics, capital, structure, leverage, profitability, tax avoidance https://doi.org/10.21632/saki.1.2.94-109